To Study Association Between Perioperative, Operative And Patient’s Factors And The Complications During Stoma Closure In Pediatrics Patients - Sharma, Ayushi; Ratre, Geetesh; Chopra, Ashok Kumar; Singh, Shashank Anil; Khati, Ayush (Journal of Neonatal Surgery, 2025)
Background: Stoma closure is a frequent elective procedure in pediatric surgery. Despite the benefits for the child, this procedure is associated with serious risks such as surgical site infection (SSI), anastomotic dehiscence, postoperative small bowel adhesions, and even mortality. Objective: The aim of this study was to audit the complications of stoma closure. The primary outcome was to determine the complication rate. The secondary outcome was to determine other associated factors. Method: This prospective observational study done in department of surgery SMS medical college Jaipur from January 2022 to January 2024, all patients at pediatric age group [less than 18years of age]. Individual patient records were reviewed to extract information prospectively. Inclusion criteria were all patients with previous stoma constructed during both elective and emergency surgery during the above time period. The following information was extracted from the patient records: patient demographics, indication for ileostomy, comorbidity status, length of hospital- stay, duration of stoma, time taken to achieve bowel movement after closure, performance status of the patient. Results: A total of 160 patients were included in the study. The median time to achieve bowel movement post closure was 3 days (range 2-16 days). The overall complication rate was 47.5%. Major complications were seen in 35% and Minor complications accounted for 25% (36/160). four patients (2.5%) died after closure from medical complications. The median follow-up duration was 10 (0–81) months. Two patient (1.6 %) died; the patient had colonic atresia and had undergone ileostomy for perforation during the neonatal period. Conclusion: stoma closure is associated with significant morbidity. While different surgeons used different preoperative antibiotic regimens, abdominal closure methods, times to NG tube removal, and times for oral feeding initiation, none of these affected the postoperative course and prognosis. In conclusion, ostomy is an important procedure that has both psychological and social impacts on the children and their families. The preoperative inpatient period and duration of antibiotic use in children can be decreased by standardization of the procedures used through the implementation of practice guidelines for each clinic and the procedure can be performed with an aesthetically more acceptable incision.